Augmented Reality: Solusi Pembelajaran IPA di Era Revolusi Industri 4.0 - Iwan Maulana; Nunuk Suryani; Asrowi Asrowi (Proceedings of The ICECRS, 2019)
Nowadays, the changes of the world are entering era of industrial revolution 4.0, which is all aspects human life depend on digital technology. Preparing qualified graduates, gaining to compete globally, mastering technological developments are important for learning especially for the future of education in Indonesia. Science is one of the subjects that is related to technology which includes aspects of products, processes, scientific attitudes, and applications. Science as a product in the form a body of knowledge consist of concepts, principles, laws, and theories must be able to contribute in creative human formation for industrial generation 4.0. Thus, the direction of development and utilization of technology in science learning should be able to help students become a superior generation, innovative, and able to compete in all fields. Augmented Reality (AR), is one of the latest technologies in the 4.0 industrial revolution that is applied in the world of education. Augmented Reality is an application of combining the real world with cyberspace in two-dimensional and three-dimensional forms projected in a real environment at the same time and is very relevant to be applied in science learning. This research method uses literature review by searching for sources that are relevant to the object of this research. Thus Augmented Reality (AR) is one solution to fix the problem of science learning in the industrial revolution era 4.0 that is able to accommodate science learning.